IMPLEMENTATION OF REHABILITATION FOR ADDICTS, ABUSERS AND VICTIMS OF NARCOTICS. - Fauzi Rizky (International Conference On Law And Social Sciences, 2024)
Implementation of Rehabilitation Narcotics refer to the provisions of Article 127 Jo Article 54 of the Law of the Republic of Indonesia Number 35 Year 2009 on Narcotics pronouncing that abusers can be proved or proved to be the victim of abuse of narcotics, Abuse Guna shall undergo medical rehabilitation and social rehabilitation and addict narcotics and victims the abuse of drugs required to undergo medical rehabilitation and social rehabilitation rehabilitation instituted both provided by the government or private parties to cooperate with the government. Implementation of rehabilitation should be qualified from the other Implementing Regulations, including already has Recommendation Integrated Assessment Team, but still banya recommendations are not running as they should. This type of research can be classified sociological law research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the National Narcotics Agency of Riau Province and the State Attorney Siak.